Phytochemical Study of Astragalus onobrychis: Bioactive Compounds, Antioxidant Activity, in silico Molecular Docking, PASS and DFT Study - Yunus Başar; Ilyas Yıldız; Ibrahim Hosaflioglu; Ramazan Erenler; Mehmet Hakki Alma (Brazilian Archives of Biology and Technology)
Abstract Astragalus species include rich bioflavonoids, triterpene glycosides, flavonoids, isoflavonoids and saponins. Astragalus species are traditionally used for diarrhea, dental treatment, diabetes treatment and as a cough remedy. In this study, the phytochemical content (total phenolic content and quantitative analysis of phenolics) and biological activity (DPPH˙) of the methanol extract of Astragalus onobrychis were investigated. The SPMB technique, a new method, was used for total phenolic and DPPH˙ analysis. Density functional theory (DFT) and theoretical in silico studies (molecular docking and PASS) were applied to the major component as kaempferol-3-glucoside (K3G) in the constituent analysis, which was performed by LC-ESI-MS/MS. Accordingly, the methanol extract of A. onobrychis was found to have high total phenolic content (FCR; 111.67 mg GA/g plant) and DPPH˙ (48.57%) analysis. Moreover, LC-ESI-MS/MS analysis revealed the K (285.011 µg/g extract) to be major constituent. In addition, the interactions of the K3G molecule with DNA mtyltransefraze 1 and urease enzyme were compared with the standard daunorubicin and thiourea. It was found that K3G may have inhibitory potential. These results can be substantiated in future studies by in vivo and in vitro studies.